1990
DOI: 10.1002/jez.1402560417
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine-nutrition interactions in birds

Abstract: This review will discuss the uses of avian models, particularly the chicken, to examine nutrition-endocrine interactions. The chicken has been employed extensively to examine nutritional effects. The effects of fasting, protein deficiency and calcium deficiency on endocrine status have been the subject of intense investigation in young chicks and adult female chickens. The ratio of circulating concentrations of triiodothyronine (T3) and thyroxine (T,) is substantially changed by fasting or protein deficiency. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 41 publications
1
6
0
1
Order By: Relevance
“…The gene products targeted by these TFs include metabolic proteins, lipid transport proteins, and those that impart hormone responsiveness on the adipocyte 18, 31. The ultimate fate of adipocyte precursor cells is determined by several factors including the immediate endocrine/paracrine environment, adhesion to the extracellular matrix, the specific milieu of transcription and regulatory factors, and nutrient availability 22, 25, 32, 33. The balances of pro- and anti-adipogenic factors present in the local environment dictate the commitment to, and progression through adipogenic cascades 34.…”
Section: Adipogenesismentioning
confidence: 99%
“…The gene products targeted by these TFs include metabolic proteins, lipid transport proteins, and those that impart hormone responsiveness on the adipocyte 18, 31. The ultimate fate of adipocyte precursor cells is determined by several factors including the immediate endocrine/paracrine environment, adhesion to the extracellular matrix, the specific milieu of transcription and regulatory factors, and nutrient availability 22, 25, 32, 33. The balances of pro- and anti-adipogenic factors present in the local environment dictate the commitment to, and progression through adipogenic cascades 34.…”
Section: Adipogenesismentioning
confidence: 99%
“…In birds, food availability is one of the major environmental factors that affect functions of endocrine systems such as the hypophysio-gonadal, -thyroidal and -adrenocortical systems (Scanes and Griminger, 1990). It is well known that starvation affects reproductive activity in various vertebrates including birds (Hosoda et al ., 1955;Morris and Nalbandov, 1961;Vigersky et al ., 1977;Brake and Thaxton, 1979;Glass and Swerdloff, 1980;Hoffer et al ., 1986).…”
Section: Introductionmentioning
confidence: 99%
“…In combination, they also found that these conditions resulted in a decreased serum T 3 level and an increased serum T 4 level, which was the reverse to that observed for chicks that were fed before cold exposure. This effect of feed restriction on the thyroid hormone levels was substantiated by King et al (1977), May (1978), Harvey and Klandorf (1983), Klandorf and Harvey (1985), Scanes and Griminger (1990), Kühn et al (1991), Darras et al (1995Darras et al ( , 1998 and Van der Geyten et al (1999). According to the study of Van der Geyten et al (1999), hepatic D 3 , an iodothyronine deiodinase that inactivates T 3 or T 4 by inner ring deiodination (St. Germain and Galton, 1997) appears to play a central role in the regulation of plasma T 3 during fasting and re-feeding in the chicken.…”
Section: Development Of Homeothermymentioning
confidence: 99%